The Importance of Cultural Heritage in Developing Students’ Visual Literacy in Art Lessons - Gadoyev Ibrohim Niyozovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the role of cultural heritage in developing students’ visual literacy in art lessons. The study examines pedagogical strategies that incorporate traditional motifs, national art forms, and historical references to enhance students’ creativity, aesthetic understanding, and artistic competencies. The article emphasizes how integrating cultural heritage into visual arts education can foster independent thinking, creative expression, and appreciation of one’s cultural identity.